Historia armenorum Transsilvaniae - Lukacsi, Christophorum (My University, 1859)
The book describes in detail the history, life, and culture of the Armenian diaspora in Transylvania from ancient times to the mid-19th century
A primordiis gentis usque nostram memoriam e fontibus authenticis et documentis antea ineditis elaborata
Christophorum Lukacsi. - Viennae : Typ. Congregationis Mechitharisticae, 1859. - 149 pages ; 23 cm.
Keywords: Armenia-History